Investigating the Potentials of Restorative Justice Practice - Lode Walgrave (Washington University Journal of Law & Policy, 2011)
The Article focuses on restorative justice programs. Topics include the efficiency of restorative justice programs compared to traditional criminal justice interventions, the effectiveness of punitive justice measures, and the variety of different restorative justice programs such as youth offender programs, communitarianism, and victims' reconciliation movements.
Keywords: Restorative justice; Criminal justice administration; Reparation (Criminal justice); Intervention (Criminal procedure); Communitarianism; Social responsibility